TYPICAL PERFORMANCE REDUCTIONS IN PV MODULES SUBJECT TO SOILING IN A TROPICAL CLIMATE (Nigerian Journal of Technology, 2020)
Soiling severely hinders the ability of solar photovoltaic (PV) modules to absorb incident solar radiation, causing significant deterioration of module performances. In this study, the thermal profiles and the electrical power outputs of PV modules were evaluated in order to establish the impact of soiling under tropical field conditions. Two case-study PV installations in the University of Nigeria were considered. Assessments of the PV systems, undertaken both when soiled and after they had been cleaned, involved the measurement of electrical power outputs and the acquisition of infrared (IR) thermograms. It was found that soiling had noticeable impacts on both module surface temperature distributions and their power outputs. The IR images, which showed spatial distributions of module surface temperatures, revealed the occurrence of hotspots on the modules when soiled. Furthermore, as a result of soiling, up to four-fold declines in module electrical efficiencies were observed. These declines were more significant in the ground-mounted PV system at the University Staff Primary School compared to the roof-mounted system at the University Energy Research Centre. Simple cleaning of the modules led to the disappearance of hotspots and significant improvements in output, showing that it is an effective means of maintaining PV modules performance and recovering the performance potentials lost due to soiling.  http://dx.doi.org/10.4314/njt.v39i4.24